SEM Analysis of Surface Layers with Variable Ra Parameters for Tribological Optimization in Design Engineering - Knast, Paweł; Petrů, Jana; Legutko, Stanislaw; Soos, Lubomir; Pokusova, Marcela (Manufacturing Technology Journal, 2025)
In this study, the microstructure of surface layers with varying roughness (Ra parameters) was analyzed using scanning electron microscopy (SEM) to optimize tribological properties in engineering design. SEM revealed key microstructural features - sharp and mild protrusions, pitting, microcracks and contaminants - that were not available in traditional profilometry. Reducing the Ra value improved surface uniformity by reducing irregularities and defect lengths, which had a positive effect on tribological properties and surface durability. However, defects were still present even at Ra < 1.25 μm, indicating the "Law of Microstructural Roughness," which emphasizes the inevitability of surface irregularities despite minimizing roughness. The integration of SEM results with profilometric methods enabled comprehensive identification and assessment of defects, combining microstructure with tribological properties. Results suggest that controlled roughness is key in combining materials and optimizing functional surfaces, particularly in the aerospace, biomedical and automotive industries, where reliability under demanding operating conditions is a priority.
Keywords: Tribology; Surface roughness; SEM analysis; Microstructural defects; Engineering design